Simultaneous Determination of Emtricitabine and Tenofovir Disoproxil Fumerate in Tablet Dosage Form by UV-Spectrophotometry - Karunakaran, Anandakumar; Kamarajan, Kannan; Thangarasu, Vetrichelvan (Asian Journal of Chemistry, 2011)
Three accurate, precise, sensitive and economical procedures for the simultaneous estimation of emtricitabine and tenofovir disoproxil fumerate in tablet dosage form have been developed. The methods employed were absorbance ratio method (I), absorbance correction method (II) and first order derivative spectroscopic method (III). The first method employs 262 nm as l1 (isobestic point) and 281 nm as l2 (lmax of emtricitabine) for formation of equations. The second method employs estimation of a drug concentration by selecting lmax where the absorbance of these drugs is maximum. But in one of the drug's lmax, the other drug has zero absorbance. So absorbance was corrected for interference. The lmax for emtricitabine and tenofovir disoproxil fumerate is 296 and 281 nm, respectively. The third method is based on first order derivative spectroscopic method. Wavelengths 298.5 nm and 226.5 nm were selected for the estimation of the emtricitabine and tenofovir disoproxil fumerate, respectively. Both the drugs obey Beer's law in the concentration range 4-24 μg/mL. The results of analysis have been validated statistically and by recovery studies.